Maternal education and tetanus immunisation in Indonesia - Wan Norsiah Mohamed, (Universiti Kebangsaan Malaysia, 1996)
This paper examines the influence of maternal education on the acceptance of tetanus toxoid vaccine, using data from two villages in rural Yogyakarta, Indonesia. Maternal education results in increased tetanus toxoid uptake. Irrespective of the level of formal education, correct knowledge of the function of tetanus toxoid is positively associated with the probability of using the vaccine. It is therefore recommended that health education campaign be run to provide correct information on the importance of tetanus toxoid. This study can be used as a model for health programmes in other population with low levels of women education.